2022
DOI: 10.1088/1741-2552/ac71ce
|View full text |Cite
|
Sign up to set email alerts
|

More than just statics: altered complexity of dynamic amplitude of low-frequency fluctuations in the resting brain after stroke

Abstract: Objective. Previous neuroimaging studies mainly focused on static characteristics of brain activity, and little is known about its characteristics over time, especially in post-stroke (PS) patients. In this study, we aimed to investigate the static and dynamic characteristics of brain activity after stroke using functional magnetic resonance imaging (fMRI). Approach.Twenty ischemic PS patients and nineteen healthy controls (HCs) were recruited to receive a resting-state fMRI scanning. The static amplitude of l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…It has been found that there were significantly altered dALFF and dReHo in multiple cortical regions in subacute stroke patients, which were related to motor function ( Chen et al, 2018 ). However, numerous studies mainly focus on supratentorial stroke patients, while little is known about the dynamic change characteristics in patients with subtentorial chronic stroke ( Liu et al, 2017 ; Tian et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that there were significantly altered dALFF and dReHo in multiple cortical regions in subacute stroke patients, which were related to motor function ( Chen et al, 2018 ). However, numerous studies mainly focus on supratentorial stroke patients, while little is known about the dynamic change characteristics in patients with subtentorial chronic stroke ( Liu et al, 2017 ; Tian et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…This is an area that we can explore in future research. Notably, the time series in this study was relatively short, comprising only 160 volumes because of the limitations of fMRI acquisition (Tian et al, 2022). In future studies, it may be beneficial to increase this duration to more accurately evaluate the dynamic changes of the participants.…”
Section: Limitation Of Studymentioning
confidence: 99%
“…In addition, study on ischemic stroke patients with dALFF also found significant changes in temporal variability of neural activity in multiple cortical regions, such as the cerebellum, Inferior temporal gyrus (IFG), dorsolateral superior frontal gyrus (SFGdl), and default mode networks (DMN), etc. ( Chen et al, 2018 ; Tian et al, 2022 ; Wang et al, 2023 ). It has a potential compensation effect on the motor dysfunction of patients.…”
Section: Introductionmentioning
confidence: 99%